Will Konaté set African journalists free? Interrogating the promises of an emerging press freedom jurisprudence in African regional courts (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: The right to freedom of expression is intrinsic to the democratic fabric of any society. This right is recognised in treaties, affirmed in political commitments and has been reiterated in the jurisprudence of judicial and quasi-judicial bodies. Despite its importance and recognition in national constitutions, the right has in various jurisdictions been subjected to severe restrictions under national law. In Africa, these restrictions are evident in a plethora of ways, including through laws on criminalisation of free speech. In recent years, however, regional adjudicatory mechanisms, including the African Court on Human and Peoples’ Rights, are increasingly pronouncing on the primacy of this freedom to democracy, offering a catalytic potential for a continent-wide shift against restrictions. This article examines the Court’s Konaté decision against the background of the Hydara and FAJ decisions of the Court of Justice of the Economic Community of West African States, and the Mseto and Burundian Journalists’ Union judgments by the East African Court of Justice. Significantly, this article finds that a common denominator in the decisions of regional adjudicatory mechanisms in Africa is the realisation that the protection of the right to freedom of expression and indeed free press is critical to African democracy. TITRE ET RÉSUMÉ EN FRANCAIS: Konaté garantira-t-il la liberté d’expression des journalistes africains? Interroger les promesses d’une jurisprudence émergente sur la liberté de presse dans les juridictions régionales en AfriqueRÉSUMÉ: Le droit à la liberté d’expression est inhérente à la fondation démocratique de toute société. Ce droit est reconnu par les traités, réaffirmé dans les engagements politiques et réitéré dans la jurisprudence des institutions judiciaires et quasijudiciaires. En dépit de son importance et de sa reconnaissance dans les constitutions, ce droit a fait l’objet, dans de nombreux pays, de sévères restrictions en droit interne. En Afrique, lesdites restrictions se manifestent sous divers jours y compris à travers les législations criminalisant la liberté de presse. Toutefois, dans les années récentes, les mécanismes de contentieux régionaux dont la Cour africaine des droits de l’homme et des peuples se prononcent de plus en plus sur l’importance de cette liberté pour la démocratie, offrant un potentiel catalytique en vue d’un mouvement contre les restrictions à l’échelle continentale. Le présent article examine l’arrêt Konaté de la Cour africaine dans une étude comparée avec ceux rendus par la Cour de justice de la Communauté Economique des Etats d’Afrique de l’Ouest dans les affaires Hydara and FAJ et par la Cour de justice de la Communauté d’Afrique de l’Est dans les affaires Mseto et Burundian Journalists’ Union. De manière notable, l’article conclut que le dénominateur commun des décisions rendues par les mécanismes de contentieux régionaux en Afrique est la conscience que la protection du droit à la liberté d’expression et, en effet, de la liberté de presse, sont des éléments fondamentaux pour la démocratie en Afrique.
Keywords: ECOWAS Community Court of Justice; East African Court of Justice; freedom of speech; freedom of expression; journalists; African Court on Human and Peoples’ Rights; democracy; Konaté